SIGNS OF THE ADMINISTRATIVE AND LEGAL REGIME IN THE SYSTEM OF EVENTS OF THE NORTHERN DELIVERY - Galina V. Goncharuk (Russian Studies in Law and Politics, 2024)
The relevance of the research lies in the strategic importance of events for early delivery of goods to hard-to-reach territories of the North and the Arctic of Russia to ensure national security, including the preservation and development of the local population. In addition, the legal regulation of early delivery of goods, which is actively developing in 2023-2024, raises the question of the administrative and legal status of northern delivery for researchers. The research attempts to substantiate the possibility of assigning the status of an administrative and legal regime to the system of northern delivery events. Accordingly, the purpose of the article is to draw conclusions about the possibility of assigning the status of an administrative and legal regime to the system of northern delivery, based on the analysis of the basic features of administrative and legal regimes defined in the dogmatic theory of law with the main characteristics of northern delivery. In conclusion of the research, the author of the article comes to the conclusion that the system of northern delivery events can be assigned the status of an administrative and legal regime, since it corresponds to its main features, subject and mechanisms.